دراسة عرض القوس السنخية العلوية والسفلية في الصنف الثاني الهيكلي بالمقارنة مع الصنف الأول الهيكلي عند البالغين (دراسة باستخدام التصوير الطبقي المحوري المخروطي ( - جحجاح يزن; عبدالله رهام (Latakia University Journal -Medical Sciences Series, 2017)
Class II malocclusion is a common clinical problem among white Caucasian population and its transverse component is a critical aspect of a functional and stable occlusion. The size and shape of the arches have considerable implications in orthodontic diagnosis and treatment planning, affecting the space available, dental esthetics, and stability of the dentition. Hence , it is important to study the alveolar arch width in this group of patients using the wide possibilities of cone beam computed tomography of evaluating real anatomy , true-to-scale images without distortions or superimpositions, and the selection of the desired sections.Objective:To evaluate the width of maxillary and mandibular alveolar arches in skelatal Class II adults compared to skeletal class I using cone beam computed tomography. Materials and methods: thirty-two subjects with skeletal Class II relationship and 10 subjects with skeletal Class I who were ordinary undergoing CBCT scan for non-orthodontics nor for otorihnolaryngology purpose were selected to measure the maxillary and mandibular alveolar width of first premolar and first molars.Independent samples’ t-test was calculated. Results:No statistically significant differences were found of alveolar widths between skeletal Class II and Class I subjects in both maxillary and mandibular widths of molar and premolar regions. Gender had no statistically significant effect in the results of the study. Conclusion :There is no differences in alveolar width between adults with skeletal Class II and Class I relationships, so the transverse discrepancy in skeletal Class II when exsists , it is more probably not originated from the alveolar base. يعتبر سوء الإطباق من الصنف الثاني مشكلة سريرية شائعة في المجتمعات ذات العرق القوقازي الأبيض ، وتشكل مظاهره في المستوى المعترض عاملا حساسا في الوصول لإطباق وظيفي مستقر. إن دراسة عرض القوس السنخية لدى هذه المجموعة من المرضى يعد هاما نظراً للدور الكبير لشكل و قياس الأقواس في التشخيص التقويمي و وضع الخطط العلاجية من ناحية تأثيرها في المسافة المتوفرة ، العوامل الجمالية السنية و استقرار الإطباق. تمكّن الخيارات الواسعة لتقنية التصوير الطبقي المحوري المخروطي من دراسة أفضل ، بما تقدمه من تحرِّ للبنى التشريحية الحقيقية , بالأبعاد ذاتها دون تشوه في المقاطع أو تراكب للبنى ، مع إمكانية اختيار المقطع المراد بكل سهولة. هدف البحث: تقييم عرض الأقواس السنخية العلوية و السفلية عند أفراد بصنف ثاني هيكلي بالمقارنة مع أفراد بصنف أول هيكلي باستخدام تقنية التصوير الطبقي المحوري المخروطي. مواد وطرق البحث: بلغ عدد أفراد العينة 42 فرداً بالغا ( 32 بصنف ثاني هيكلي ، 10 بصنف أول هيكلي) لم يخضعوا لمعالجة تقويمية سابقة و تم انتقاؤهم من مرضى كانوا تلقائيا بصدد إجراء تصوير طبقي محوري مخروطي لأسباب غير تقويمية و لا تتعلق بأمراض الأذن و الأنف و الحنجرة ، تم قياس العرض السنخي عند الضواحك و الأرحاء الأولى العلوية و السفلية ، تم تطبيق اختبار t للعينات المستقلة . النتائج : لا يوجد فرق ذو دلالة إحصائية بين العرض السنخي العلوي و السفلي لدى أفراد الصنف الأول و الثاني الهيكلي في منطقة الضواحك و الأرحاء . لم يكن للجنس تأثير ذو دلالة إحصائية في نتائج الدراسة. الخلاصة : لا يوجد فرق في العرض السنخي بين البالغين من الصنف الثاني و الصنف الأول الهيكلي و بالتالي فإن منشأ الخلل في المستوى المعترض عند أفراد الصنف الثاني الهيكلي -عند وجوده- لا يعود غالبا للقواعد السنخية .